Cure of Psoriasis and Arthritis when Addison's Disease Was Detected - Marcus Lind (Karger Publishers, 2010)
Introduction: Corticoid therapy is well-known to improve the symptoms of psoriasis. Addison's disease is an autoimmune disease which leads to a loss of cortisol production in the adrenal glands. This case report describes a patient with wide-spread psoriasis for 34 years who was cured when Addison's disease was detected and substitution to reach normal biological cortisol levels was introduced. Case Report: A 59-year-old man was diagnosed with Addison's disease. He had been tired for several years and had had difficulties in continuing his work. His brother had Addison's disease and recommended him to make a screen for the disease. Synacthen test diagnosed Addison's disease with a clear deficiency of cortisol production. After substitution with hydrocortisone the patient's constitution improved rapidly and he felt no longer tired during work. At the same time, all skin lesions of psoriasis disappeared as well as aches in several joints, both symptoms having been present for a couple of decades. Previously, salves of cortisol had been used to reduce the symptoms of psoriasis, but now, 1-2 years later, after the treatment of Addison's disease, no symptoms in the skin or joints have reoccurred. Conclusions: This report illustrates that Addison's disease, although a rare condition, should be kept in mind before treatment of psoriasis is started. Especially if other symptoms such as fatigue are present, a screening test of serum cortisol in the morning should be liberally made. The report also illustrates a need of examining corticoid levels in patients with psoriasis compared to the general population.